Nodular lymphoid hyperplasia: A thin grey zone between hyperplasia and Pathological aggregate - Brij Mohan Kumar Singh; Arijit Bishnu; Tanvi Shetty; Panna Shetty (Tropical Journal of Pathology and Microbiology, 1970)
Introduction: The clinical-pathological characteristics of 12 patients with intestinal nodular lymphoid hyperplasia (NLH) are described with the aim to try and delineate between hyperplasia and pathological aggregate of lymphoid tissue in the intestine and its association with other diseases from Indian subcontinent.Materials and Method: 12 diagnosed cases of NLH were retrieved out of 2256 intestinal punch biopsy done at our centre and were evaluated as per histological criteria laid down by various authors including their clinical and pathological features.Results: Most frequent symptom includes diarrhoea and weight loss and the severity of these symptoms were directly proportional to the number and location of the lymphoid nodules. Prominent lymphoid nodules in mucosa and/or submucosa were documented histologically in all cases. One patient had associated common variable immunodeficiency which on follow up developed intestinal lymphoid malignancy of NHL type (DLBCL) and the other was having hypogammaglobulinemia. All cases showed absence of plasma cells, except one with predominant symptoms of Gastro-esophageal reflux disease (GERD) rather than diarrhea.Conclusion: NLH runs as a benign course, but these cases should be followed up with histology as well as thorough clinical and biochemical evaluation to detect early lymphoma that can be managed efficiently.